Pengaruh Faktor Fisiologis, Lingkungan Sekolah, dan Motivasi Belajar Terhadap Hasil Belajar Ekonomi Di SMAN 2 Painan - Rika Dewi; Marwan Marwan (Jurnal Ecogen, 2019)
This study aims to: 1) To see the effect of physiological factors on students 'economic learning motivation, 2) To see the influence of the school environment on students' economic learning motivation, 3) To see the effect of physiological factors on student economic learning outcomes, 4) To see the effect school environment on student economic outcomes, 5) To see the effect of student learning motivation on student economic learning outcomes. This type of research is associative descriptive research. The sample used as many as 90 people using Nonprobability Sampling. Data collection techniques used were observation and questionnaire / questionnaire. The collected data were analysis with the help of SPSS 21.0 program. This research uses path analysis. The results of this study indicate that 1) physiological factors significantly influence students' economic learning motivation, 2) School environment has a significant effect on students' economic learning motivation, 3) Physiological factors significantly influence students' economic learning outcomes, 4) School environment has a significant effect on student economic learning outcomes, 5) learning motivation has a significant effect on economic learning outcomes of students of class XI IPS SMAN 2 PainanKeyword: physiological, school environment, learning motivation, learning outcomes.